Predicting and Preventing Loss to Follow-up of Adult Trauma Patients in Randomized Controlled Trials: An Example from the FLOW Trial. (5th July 2017) - Madden, Kim; Scott, Taryn; McKay, Paula; Petrisor, Brad A.; Jeray, Kyle J.; Tanner, Stephanie L.; Bhandari, Mohit; Sprague, Sheila
Abstract : Background: High loss-to-follow-up rates are a risk in even the most rigorously designed randomized controlled trials (RCTs). Consequently, predicting and preventing loss to follow-up are important methodological considerations. We hypothesized that certain baseline characteristics are associated with a greater likelihood of patients being lost to follow-up. Our primary objective was to determine which baseline characteristics are associated with loss to follow-up within 12 months after an open fracture in adult patients participating in the Fluid Lavage of Open Wounds (FLOW) trial. We also present strategies to reduce loss to follow-up in trauma trials. Methods: Data for this study were derived from the FLOW trial, a funded trial in which payments to clinical sites were tied to participant retention. We conducted a binary logistic regression analysis with loss to follow-up as the dependent variable to determine participant characteristics associated with a higher risk of loss to follow-up. Results: Complete data were available for 2, 381 of 2, 447 participants. One hundred and sixty-three participants (6.7%) were lost to follow-up. Participants who received treatment in the U.S. were more likely to be lost to follow-up than those who received treatment in other countries (odds ratio [OR] = 3.56, 95% confidence interval [CI]: 2.46 to 5.17, p < 0.001). Male sex (OR = 1.75, 95% CI: 1.15 to 2.67, p = 0.009), current smoking (OR = 1.82, 95% CI: 1.28 to 2.58, p = 0.001), high-risk alcohol consumption (OR = 1.88, 95% CI: 1.16 to 3.05, p = 0.010), and an age of <30 years (OR = 2.16, 95% CI: 1.19 to 3.95, p = 0.012) all significantly increased the odds of a patient being lost to follow-up. Conversely, participants who had sustained polytrauma (OR = 0.52, 95% CI: 0.37 to 0.73, p < 0.001) or had a Gustilo-Anderson type-IIIA, B, or C fracture (OR = 0.60, 95% CI: 0.38 to 0.94, p = 0.024) had lower odds of being lost to follow-up. Conclusions: Using a number of strategies, we were able to reduce the loss-to-follow-up rate to <7%. Males, current smokers, young participants, participants who consumed a high-risk amount of alcohol, and participants in the U.S. were more likely to be lost to follow-up even after these strategies had been employed; therefore, additional strategies should be developed to target these high-risk participants. Clinical Relevance: This study highlights an important need to develop additional strategies to minimize loss to follow-up, including targeted participant-retention strategies. Male sex, an age of <30 years, current smoking, high-risk alcohol consumption, and treatment in a developed country with a predominantly privately funded health-care system increased the likelihood of participants being lost to follow-up. Therefore, strategies should be targeted to these participants. Use of the planning and prevention strategies outlined in the current study can minimize loss to follow-up in orthopaedic trials.